Pharmacological Effects of Curcumin in Chronic Inflammatory Therapy - Muntasir, Muntasir; Faradina, Anggia; Wuryandari, Tutik; Cendekiawan, Khrisna Agung (Pt. Anagata Sembagi Education, 2025)
Herbal plants Herbal plants in Indonesia have an important role in traditional medicine and public health. The study aims to evaluate the effectiveness and mechanism of action of curcumin in chronic inflammatory therapy. This study employs the Systematic Literature Review (SLR) methodology.. This study uses a database from Scopus of 9 Scopus articles from the range of 2020 to 2025. There are three stages carried out in mapping the effectiveness and mechanism of action of curcumin in chronic inflammatory therapy, namely data harvesting, screening data and Data Analysis and Visualization. The results obtained are that curcumin is effective in chronic inflammatory therapy by inhibiting the main inflammatory pathways (NF-ƙB and JAK/STAT), has antioxidant effects, accelerates tissue regeneration, and functions as an immunomodulator. However, the limited bioavailability of curcumin presents a significant challenge in its application. Nanoformulation technology and its combination with compounds like CMPs can enhance its effectiveness in clinical therapy.The implications of this research are directed to researchers, the community and the government